Geographic areas of responsibility among PCI-capable hospitals in the Philippines. (25th January 2023) - Toledano, B; Garganera, K B; Prado, J P; Sabas, M L; Gregorio, G S
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The archipelagic nature of the Philippines is unique and the geographic areas of responsibility for ST elevation myocardial infarction patients should be defined. Methodology: The list of registered PCI capable hospitals and the total members of adult interventional cardiologists per island from the Philippine Society of Cardiac Catheterization Incorporation as of January 2022 was used. Their characteristics were described using frequency and percentage. The web application Map Developers was utilized to locate the exact location of each PCI-capable center and a 120km radius at the center of each PCI-capable hospital was drawn. The 120km radius was based on the average of 60km/hour from the Land Transportation & Traffic code multiplied by 2 hours based on the maximum expected delay from STEMI diagnosis to primary PCI. The map of Philippine provinces was obtained from the Creative Commons Attribution-Share Alike 4.0 international file name Ph administrative map blank. The maps of the geographic area of responsibility and provinces were interposed using MS PowerPoint version 2201 and categorized as covered, partially covered, and not covered. Results: The analysis included a total of 3 islands with 82 provinces, 244 adult interventional cardiologists (IC) and 54 PCI-capable hospitals. The region registered the highest percentage of IC (85.7%) and PCI-capable hospitals (78.9%) followed by Visayas (8.6%) and (11.5%), and Mindanao (5.7%) and (9.6%) respectively. Most PCI-capable hospitals are privately (79.6%) versus government owned (20.4%). Most percentage of PCI-capable hospitals are in Metro Manila (46.3%), followed by Cebu (9.26%), Laguna and Pampanga (5.57%), Benguet, Davao del Sur, Misamis Oriental, Nueva Ecija and Iloilo (3.7%). Only 46.4% of the provinces are covered, 34.1% are partially covered and 19.5% are not covered. Conclusion: In the Philippines, most PCI-capable hospitals are privately owned and centrally located on an island. There may be a need to add PCI-capable hospitals that are government owned, equally distributed, and strategically placed in partially and non-covered provinces. In addition, due to its archipelagic nature, STEMI patients in other provinces that are not covered may benefit from rapid fibrinolysis. Map of PCI capable hospitals & provinces Coverage of PCI capable hospitals